Interfacial Electrostatic Self‐Assembly of Amyloid Fibrils into Multifunctional Protein Films. Issue 9 (25th January 2023) - Han, Yangyang; Cao, Yiping; Zhou, Jiangtao; Yao, Yang; Wu, Xiaodong; Bolisetty, Sreenath; Diener, Michael; Handschin, Stephan; Lu, Canhui; Mezzenga, Raffaele
Abstract: Amyloid fibrils have generated steadily increasing traction in the development of natural and artificial materials. However, it remains a challenge to construct bulk amyloid films directly from amyloid fibrils due to their intrinsic brittleness. Here, a facile and general methodology to fabricate macroscopic and tunable amyloid films via fast electrostatic self‐assembly of amyloid fibrils at the air–water interface is introduced. Benefiting from the excellent templating properties of amyloid fibrils for nanoparticles (such as conductive carbon nanotubes or magnetic Fe3 O4 nanoparticles), multifunctional amyloid films with tunable properties are constructed. As proof‐of‐concept demonstrations, a magnetically oriented soft robotic swimmer with well‐confined movement trajectory is prepared. In addition, a smart magnetic sensor with high sensitivity to external magnetic fields is fabricated via the combination of the conductive and magnetic amyloid films. This strategy provides a convenient, efficient, and controllable approach for the preparation of amyloid‐based multifunctional films and related smart devices. Abstract : Multifunctional amyloid films via fast electrostatic self‐assembly of amyloid fibrils at the air–water interface are designed. A magnetically oriented soft robotic swimmer with well‐confined movement trajectory, and smart magnetic sensing devices with high sensitivity are fabricated, which can be used for real‐time detection and continuous monitoring of external magnetic fields.